Examining the impact of culture, transnationalism, globalization and product involvement on customer purchase behavior of Japanese anime products - Chen, Johnson Wang (Animo Repository, 2023)
As anime gains popularity, businesses seek to capitalize on the medium's appeal. A recent study explored the impact of anime collaboration items on customer purchase intention, examining the factors that influence consumers' behavior when purchasing anime-related merchandise. Additionally, the study analyzed the effects of culture, transnationalism, and globalization on consumer purchasing behavior, the study was conducted to help businesses understand their customers and most effective ways to reach them. The researchers investigated variables like budgeting, product comparison, actual purchasing, and subsequent thoughts, feelings, and behaviors to provide businesses with more specific information on purchasing factors that influence consumers' behavior. This information can help firms develop new ideas for promoting anime collaboration products while taking consumer interests and desires into account. By studying cultural, transnational, and globalization effects on anime-related purchases, businesses can create unique sales tactics that connect better with their target audience, including advertising and distribution strategies. The study's findings can eventually inform organizations' sales management decisions, providing them with a deeper understanding of selling products that connect effectively with their target audience. The study underscores the importance of understanding consumer behavior when selling anime collaboration products, and how businesses can adapt sales strategies to capitalize on anime's growing popularity.